Managing Acute Kidney Injury in Severe Falciparum Malaria: Insights from a Challenging Case - Dominikus Evano Putra; Indra Kasman; Angela Merici Bunga Boro; Asep Purnama; Eddy Zulfikar (Iranian Journal of Parasitology, 2025)
Malaria continues to pose a significant public health challenge, particularly in certain regions of Indonesia, where it remains endemic. Plasmodium falciparum is responsible for the most severe form of the disease, often leading to life-threatening complications such as acute kidney injury (AKI). Here, we report the case of a 22-year-old male from Sikka Regency, East Nusa Tenggara, Indonesia, with a seven-day history of intermittent fever following recent travel to malaria-endemic areas. On physical examination, he appeared somnolent and exhibited icteric sclera, hepatomegaly, and dark yellow urine. Laboratory findings were notable for impaired kidney function (serum creatinine 3.52 mg/dL (311 μmol/L)), elevated transaminases, hyperbilirubinemia, thrombocytopenia, and a P. falciparum parasitemia level of 9.7%. Imaging studies revealed pulmonary edema, enlarged kidneys, ascites, pleural effusion, and hepatomegaly. The patient was diagnosed with severe falciparum malaria, complicated by AKI, pulmonary edema, and jaundice. He was then treated with intravenous artesunate for six days, followed by a three-day course of oral dihydroartemisinin/piperaquine and a single dose of primaquine. Additionally, he underwent two sessions of timely hemodialysis. His clinical condition and kidney function gradually improved thereafter, and he was discharged without sequelae. This case highlights that early diagnosis and appropriate treatment can lead to full recovery from AKI caused by severe P. falciparum malaria.